The correlation of functional pain and psychological distress: a study in Italian school students - Margherita Lo Curto; Maria Cristina Maggio; Fabio Campisi; Giovanni Corsello (Italian Journal of Pediatrics, 2019)
Abstract Background Functional Pain (not detectable organic cause) is often associated with psychological problems and, according to literature, it can lead to severe manifestations. The purpose of the study was to investigate the correlation between functional pain and psychological disagreement, in a series of school students. Methods An observational questionnaire-based study was performed. A questionnaire was given to a group of students of primary school; the following data were collected in the questionnaire: a) sex and age; b) functional pain; c) relation with relatives, teachers and schoolfellows: d) school failure. Statistical methods: P-value of concordance test and P-value of correlation have been performed with MINITAB 15.1 software. Results Eight hundred nine students, 354 females, 455 males, median age 14 years, participated to the study. Functional Pain was referred from 537/809 students (66%): 265 Females, 272 males: p = 0.155. The difference between the number of pain episodes in females vs. males was statistically significant (p = 0,511), as pain intensity vs. the number of episodes in females (p = 0.001). The most frequent location of pain was abdomen in females, limbs in males. Psychological disagreement was referred from 513/809 students (63%) (260 females; 253 males: p = 0,150). Psychological disagreement was reported with parents (19); siblings (22); other relatives (18); teachers: 42, schoolfellows: 366, relatives as well as school fellows: 46. The correlation between disagreement and functional pain in all the students included in the study was statistically significant (p < 0.001). Conclusions most students reported psychological disagreement and pain. The most frequent cause of disagreement was schoolfellows’ behaviour. The study shows a student’s lack of discussing of their problems with parents, teachers, peer. According to literature, confiance would be a useful treatment for avoiding psychological disagreements and functional pain.